ECOLOGICAL THEOLOGY IN GMIH LITURGY AND ITS ROLE AS THE CHURCH’S EDUCATIONAL RESPONSIBILITY TOWARD THE ENVIRONMENTAL CRISIS IN NORTH MALUKU - Yulianus Serang; Marton Tasiringan; Indri Katengar (STT Bethel Indonesia Jakarta, 2026)
The purpose of this study is to describe the Church's strategy for developing a Pentecostal spirituality and Divine Healing experience for Generation Alpha, based on the Book of Acts. Raised entirely in a digital ecosystem, this generation strongly desires to feel and experience the truth of the Word made real in their lives. The church must create new ministry platforms, especially in virtual spaces, to teach and provide understanding of true Pentecostal spirituality and Divine Healing. The research employed a qualitative approach using textual analysis methods. The results highlight the church's contextual approach, translating its message verbally and digitally (Acts 2:7-11); a relational approach, building a healing and empowering community (Acts 2:44, 46); adaptation to technology, using social media for mission and healing ministry (Acts 5:12-16); and providing space for Generation Alpha's spiritual growth (Acts 19:13-20). The Church must focus on the Word to maximise the practical experience of the Holy Spirit and Divine Healing for Generation Alpha.